1926
DOI: 10.1192/bjp.72.296.66
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Immunity to Malarial Inoculation

Abstract: In connection with the malarial treatment of general paralysis of the insanein thishospital, we have endeavouredto producea secondseriesof malarialrigorsin such casesas had not shown sufficient mental or physical benefit after a first infection terminated six or more months ago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The slowness with which antiparasitic mechanisms consolidate has often been taken as evidence that plasmodial populations in hyperendemic areas comprise many antigenically distinct species and strains, most of which have to be experienced before an effective antiparasite immunity is acquired ( Hackett 1941). However, during malariotherapy, good evidence was produced that partial clinical protection after challenge was evident not only to the homologous strain, but also towards heterologous strains of the same species ( Nicole & Steel 1926). This was further reinforced by the observations that in passive transfer studies, IgG from West African immune serum protected against P. falciparum parasites of East African origin ( McGregor et al .…”
Section: Introductionmentioning
confidence: 99%
“…The slowness with which antiparasitic mechanisms consolidate has often been taken as evidence that plasmodial populations in hyperendemic areas comprise many antigenically distinct species and strains, most of which have to be experienced before an effective antiparasite immunity is acquired ( Hackett 1941). However, during malariotherapy, good evidence was produced that partial clinical protection after challenge was evident not only to the homologous strain, but also towards heterologous strains of the same species ( Nicole & Steel 1926). This was further reinforced by the observations that in passive transfer studies, IgG from West African immune serum protected against P. falciparum parasites of East African origin ( McGregor et al .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this was the results of artificial challenges during malaria therapy, which conferred partial clinical protection both to homologous and heterologous inocula. 9 Passive transfer studies have also demonstrated also that sera from west Africans can confer protection against east African P. falciparum parasites. 10 In contrast to this view, the slow pace at which anti-parasitic mechanisms develop has been used to suggest that plasmodial populations comprise many antigenically distinct genotypes, that clinical immunity is largely specific to genotypes, and that the child becomes immune as he or she is exposed sequentially to different genotypes.…”
mentioning
confidence: 99%